The Effect of Support Groups on Social Support and Psychological Well-Being Among Young People Living with HIV in Inti Muda West Java - Riki Jakaria; Prinska Damara Sastri; Pratidina Ekanensia (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Young people living with HIV face significant psychosocial challenges that require effective interventions such as support groups. However, to date, there has been no simultaneous quantitative empirical evaluation of the effectiveness of such interventions within community-based organizations in Indonesia. Therefore, the novelty of this study lies in its integrative examination of the impact of structured support groups on social support and psychological well-being specifically among the Inti Muda community in West Java. This one-group pretest-posttest quasi-experimental study involved participants aged 18–35 years who were selected through purposive sampling. The intervention consisted of five structured sessions over five weeks that integrated peer support, psychoeducation, and Yalom’s therapeutic factors. Measurements were taken using the Multidimensional Scale of Perceived Social Support and Ryff’s Psychological Well-Being Scale. Analysis results showed a significant increase in the mean pre- and post-intervention scores for social support and psychological well-being (p = 0.043). In conclusion, the support group proved to be effective, and these findings provide an important foundation for the development of structured, community-based psychosocial interventions aimed at improving the quality of life for young people living with HIV.